Endoscopic mucosal healing and histologic remission in ulcerative colitis: a systematic literature review of clinical, quality-of-life and economic outcomes. (2nd September 2022) - Pandey, Anuja; Achrafie, Lea; Kodjamanova, Petya; Tencer, Tom; Kumar, Jinender
Abstract: Objective: This systematic literature review (SLR) assessed the effects of endoscopic mucosal healing and histologic remission on clinical, quality-of-life (QoL), and economic outcomes in adults with ulcerative colitis (UC) in the real-world setting. Methods: Literature searches of Embase and MEDLINE (6 July 2020) and conference proceedings (2017–2020) were performed according to Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Eligible studies included adults with UC with documented endoscopic mucosal healing or histologic remission. Clinical, QoL, and economic outcomes were extracted and narratively synthesized. Results: Of 1603 studies screened, 25 met eligibility criteria and collectively included 2813 patients (mean age: 34–60 years). The most commonly reported indices were Mayo endoscopic score (MES) for endoscopic mucosal healing ( n  = 22, 88%) and Geboes score ( n  = 5, 20%) for histologic outcomes. The most frequently reported clinical outcome was relapse-free survival ( n  = 15, 60%). Less commonly reported outcomes were avoidance of colectomy ( n  = 5, 20%), hospitalization ( n  = 4, 16%), clinical remission ( n  = 4, 16%), and steroid-free clinical remission ( n  = 3, 12%). Most studies reported relapse-free survival rates up to 50% over 6–48 months of follow-up in endoscopic mucosal healing cohorts. Studies reporting results by MES demonstrated higher relapse-free survival rates among patients with MES 0 than with MES 1 (32%–100% vs 26%–86%, respectively). Similarly, patients with histologic remission had better relapse-free survival rates over 12–24 months of follow-up compared with those without histologic remission (72%–91% vs 40%–63%, respectively). Rates of clinical remission, steroid-free remission, hospitalization, and colectomy avoidance were also better among patients with endoscopic mucosal healing and histologic remission. Two studies examining QoL reported endoscopic mucosal healing was associated with improved QoL. No study reported economic outcomes. Conclusions: This SLR demonstrated consistent evidence of improved clinical outcomes among UC patients with endoscopic mucosal healing and histologic remission. PLAIN LANGUAGE SUMMARY: Ulcerative colitis (UC) is a chronic, relapsing disease characterized by inflammation of the mucous membranes lining the rectum and colon. While medical management has traditionally focused on lessening UC symptoms, there is growing recognition that the reduction of underlying inflammation visible endoscopically (called endoscopic mucosal healing) or microscopically (called histologic remission) can be an objective indicator of disease improvement. This research is the first systematic literature review to assess the effects of endoscopic mucosal healing and histologic remission on clinical, quality-of-life (QoL), and economic outcomes in adults with UC in the real-world setting. We included studies in adults with UC who had mucosal healing or histologic remission and analyzed clinical, QoL, and economic outcomes using a technique called narrative synthesis. Twenty-five of 1603 studies screened met our eligibility criteria for inclusion in the analysis. In most studies, over 50% of patients with endoscopic mucosal healing did not relapse during follow-up, with better relapse-free survival rates reported among patients with a Mayo endoscopic scores of 0 than among those with a score of 1. Likewise, patients with histologic remission had higher relapse-free survival rates than those without histologic remission. Rates of clinical remission, steroid-free remission, hospitalization, and colectomy avoidance were better among patients with mucosal healing and/or histologic remission. Two studies also reported better QoL outcomes. Our findings suggest that endoscopic mucosal healing or histologic remission is associated with improved clinical and QoL outcomes. While more information is required, these measures should be considered important when making therapeutic decisions for patients with UC.